2018
DOI: 10.1002/anie.201800167
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of Astellatol

Abstract: A nearly-30-year-old unanswered synthetic puzzle, astellatol, has been solved in an enantiospecific manner. The highly congested pentacyclic skeleton of this rare sesterterpenoid, which possesses a unique bicyclo[4.1.1]octane motif, ten stereocenters, a cyclobutane that contains two quaternary centers, an exo-methylene group, and a sterically encumbered isopropyl trans-hydrindane motif, makes astellatol arguably one of the most challenging targets for sesterterpenoid synthesis. An intramolecular Pauson-Khand r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…[7c-e] Thet riethylsilyl group was cleaved concomitantly.I nterestingly,w hen this reaction was scaled up to 150 mg or higher scale,the diastereoselectivity was somehow decreased (5:1). Other hydrogenation attempts,u sing for example,C rabtreesc atalyst [24] or Wilkinsonsc atalyst, [25] resulted in either undesirable diastereoselectivity or no reaction. Subsequent addition of 2-hydroxy-2-azaadamantane (AZADOL) and (diacetoxyiodo)benzene( PIDA) to the reaction mixture led to ao ne-pot oxidation, affording enone 18 in 82 %y ield.…”
Section: Methodsmentioning
confidence: 99%
“…[7c-e] Thet riethylsilyl group was cleaved concomitantly.I nterestingly,w hen this reaction was scaled up to 150 mg or higher scale,the diastereoselectivity was somehow decreased (5:1). Other hydrogenation attempts,u sing for example,C rabtreesc atalyst [24] or Wilkinsonsc atalyst, [25] resulted in either undesirable diastereoselectivity or no reaction. Subsequent addition of 2-hydroxy-2-azaadamantane (AZADOL) and (diacetoxyiodo)benzene( PIDA) to the reaction mixture led to ao ne-pot oxidation, affording enone 18 in 82 %y ield.…”
Section: Methodsmentioning
confidence: 99%
“…Xu and co‐workers reported the first enantiospecific total synthesis of astellatol 273 (Scheme 28), [207] a fascinating sesterterpenoid with sterically congested trans ‐hydrindane framework, extracted from Aspergillus stellatus . Biological properties of astellatol are still undisclosed and only limited synthetic studies have been reported by Xu [208] and Trauner's [209] groups.…”
Section: Ring‐closing Metathesis (Rcm)mentioning
confidence: 99%
“…As a result, the total synthesis of the rare sesterterpenoid, astellatol 544, was achieved in twenty-ve steps and 0.63% overall yield starting from chiral synthon 524 (Scheme 42). 366,371 A concise and asymmetric total synthesis of A-ring component of nitiol 559 including diastereoselective Pauson-Khand cycloaddition was reported by Dake in 2001. 372 It was actually an attempt towards the total synthesis of the natural product, nitiol 558.…”
Section: Sesquiterpenoidsmentioning
confidence: 99%
“… 365 In 2018, Xu et al also accomplished 536 (ref. 366 ) and reported a brief and asymmetric synthesis of astellatol 544. That was including a SmI 2 -catalyzed reductive radical 1,4-addition.…”
Section: Applications Of Pauson–khand Reaction In the Total Synthesis...mentioning
confidence: 99%
See 1 more Smart Citation